CORPORATE GOVERNANCE MECHANISMS AND FINANCIAL REPORTING QUALITY: THE ROLE OF AUDIT COMMITTEE MEETINGS AND INSTITUTIONAL OWNERSHIP IN INDONESIAN BANKS - Sari Lestari; Ferdiansyah Ritonga (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to analyze the effect of audit committee meeting frequency and institutional ownership on earnings management in banking sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This study employs a quantitative approach using secondary data obtained from the companies’ annual reports and financial statements. The sample was determined using a purposive sampling technique, resulting in 16 companies with a total of 80 observations. Data analysis was conducted using panel data regression. The control variables used in this study were firm size, leverage, and profitability. The results indicate that institutional ownership has a significant negative effect on discretionary accruals, while profitability has a significant positive effect on discretionary accruals. Meanwhile, audit committee meeting frequency, firm size, and leverage have negative but statistically insignificant effects. Simultaneously, all independent variables significantly affect discretionary accruals. These findings suggest that corporate governance mechanisms, particularly institutional ownership, play a role in influencing earnings management practices in banking companies.